Menakar efektivitas kompetensi profesional guru dan motivasi belajar dalam meningkatkan prestasi belajar ekonomi siswa SMA - Natanael Raka Anantyo; Sudarno Sudarno; Muhammad Sabandi (Jurnal Pendidikan Ekonomi (JUPE), 2025)
This study aims to assess the effectiveness of teachers’ professional competence and students’ learning motivation in improving academic achievement in high school Economics. Employing a quantitative approach with a survey design, the study involved 283 randomly selected students from grades X to XII at Senior High School State 2 Sukoharjo during the 2024/2025 academic year. Data were collected using a closed-ended Likert-scale questionnaire and analyzed through multiple linear regression using SPSS version 27. The results indicate that both teacher professional competence and student motivation significantly influence students’ achievement, both jointly and individually. Among these, teacher competence is more dominant in explaining variations in student outcomes. These findings highlight the need to strengthen teacher capacity and implement learning strategies that foster students’ intrinsic motivation as key efforts to enhance instructional quality at the senior high school level. The study is limited by the scope of its variables and reliance on perception-based data; future research is recommended to incorporate qualitative approaches and contextual factors for more profound insight.